Study on the Effects of Plastic as Admixture on the Mechanical Properties of Cement-Sand Bricks - Fai Chow M.; Khalili Rosidan M.A. (Institute of Physics Publishing, 2023)
Cement-sand bricks is one of the building materials that being used as alternative for a low-cost house in Malaysia. Nowadays, many researchers have been researching for green and sustainable materials to replace conventional building materials. In this paper, plastic bottle has been studied as a new alternative admixture in cement-sand brick production. The objective of this research is to determine the effect of plastic size on mechanical properties of cement-sand bricks. The lab testing used for this research are compressive strength and water absorption tests. Based on the findings, the bigger size of plastic added into the brick mixture, the higher compressive strength can be achieved. This is due to the plastic can increase the structural integrity of the cement-sand brick. Also, the bigger size of plastic added into the mixture, lower rate of water absorption was obtained. This may be due to plastic help in reducing the volume of void of the cement-sand brick. Further studies are needed to improve the cement-sand brick production with plastic as admixture material. Published under licence by IOP Publishing Ltd.